Real-time continuous glucose monitoring versus self-monitoring of blood glucose in adults with insulin-treated type 2 diabetes: a protocol for a randomised controlled single-centre trial - Kirsten Nørgaard; Nanna Lind; Dorte Lindqvist Hansen; Signe Sætre Rasmussen (BMJ Open, 2021)
Introduction Medical treatment options for type 2 diabetes (T2D) have increased over the last decade and enhance the possibility of individualised treatment strategies where insulin is still one of them. In spite of the advancements in treatment options, less than one-third of the population with T2D obtain their optimal glycaemic goal. In persons with type 1 diabetes, continuous glucose monitoring (CGM) has shown to be the most important driver for improvement in glycaemic control, even more than insulin-pump therapy. The use of technology in T2D has only been investigated in few studies.The overall objective of the research study is to examine the effectiveness of the use of CGM versus self-monitoring of blood glucose (SMBG) in persons with insulin-treated T2D on glycaemic variables and patient-reported outcomes on treatment satisfaction, health behaviour and well-being. The independent effect of peer support will also be studied.Methods and analysis The study is a single centre, prospective, randomised, open-labelled, three-armed study with the randomisation 2:1:2 in group A with CGM, group B with CGM and peer support, and group C as a control group with SMBG. The participants receive a training course unique for the allocation group. The study runs for 12 months and includes 100 adult participants with insulin-treated T2D, treated at the outpatient clinic at Steno Diabetes Center Copenhagen. Primary outcome is difference in change in time in range. Recruitment begins in August 2020 and ends in July 2021. Final 12-month follow-up is anticipated to be in August 2022.Ethics and dissemination The study will be carried out in accordance with the Helsinki Declaration and is approved by the Scientific Ethics Committee of the Capital Region (H-20000843). Data collection and handling will be performed in accordance with the General Data Protection Regulation and is approved by the Danish Data Protection Agency (J-2020-100). Dissemination will be in international peer-reviewed journals, conferences and a plain-language summary for participants.Trial registration number ClinicalTrials.gov Registry (NCT04331444).Protocol version V.3, 11 December 2020.